Musculoskeletal Injuries in Volleyball Players - Probyn, Linda; Flores, Dyan; Beaulieu, Christopher; Atinga, Angela (Seminars in Musculoskeletal Radiology, 2025)
Volleyball is a very popular sport worldwide, and both the indoor and outdoor versions are played at the Olympics. The several different positions have unique associated injuries. Some positions require fast movements and reflexes; others require strength and power. Given the repetitive jumping and shoulder movements, some of the positions are susceptible to chronic overuse injuries. Others are related to landing awkwardly or taking powerful hits/blocks from the ball. Indoor volleyball, played on a firm surface, has more of an impact on players compared with beach volleyball played on sand. This article describes the fundamental positions and moves in volleyball, the differences between indoor and beach volleyball, the common risk factors, and specific injuries related to the upper extremity, lower extremity, and axial skeleton.
Keywords: volleyball; sports injuries; imaging